고압 나트륨램프의 점등과 소등을 위한 제어기의 릴레이 접점의 융착 방지 - 韓泰煥(Tae-Hwan Han); 禹天熙(Chun-Hee Woo) (전기학회 논문지 P권, 53(3), 2004)
For turn on high pressure sodium vapor lamp, Starting Voltage is very important factor. This starting voltage supply to high pressure sodium vapor lamp as electric discharge lamp, Electric field is producted in electric discharge tube, So accelerative electron collide against vapor atom and second electron is generated, And rapidly the current flow to electric discharge tube. This starting voltage is high voltage and source for melting contact that relay is according as turn on/off high pressure sodium vapor lamp. Consequently, This paper propose that the prevention of melting contact in accordance relay of controller for turn on/off high pressure sodium vapor lamp.